HISTORICAL RELATIONS OF FLORES LANGUAGE KINSHIP: (A Comparative Historical Linguistic Study of Nine Languages in Flores) - Sugeng Raharja; Rawuh Yuda Yuwana (Acceleration: Multidisciplinary Research Journal, 2023)
A Comparative Historical Linguistic Study of Nine Languages in Flores aims to prove the typology relationship of Flores languages. This research focuses on the typological linguistics study of nine Flores languages. The method in this study is descriptive qualitative-comparative. The results of this study reveal that the Flores languages (Km, Mg, Rb, Ng, Li, Pl, Sk, Lh, and Kd are related. The qualitative evidence is shown by phonological and lexical innovations experienced by the Flores language group at the Proto, Meso, and lower levels. Then, based on the typological linguistic study of 9 Flores languages that are the object of Fernandez's study can be said to be a language group based on genetic typology. However, the research results published by Nusa Indah publisher do not mean they have no shortcomings. Some of the shortcomings in question are not fatal errors, but readers who primarily do not have a linguistic or scientific background will experience a little confusion. Finally, Fernandez's rebuttal to previous research related to language grouping in the archipelago, by calling a single criterion in the form of specific syntactic characteristics as an inappropriate criterion seems to have to be straightened out. Considering the point of view of language typology, studies between syntactic criteria and criteria used in LHK have different final results. The first grouped languages based on the language's internal structure, while LHK looked at and grouped languages based on lineage.